Polyphenolic compounds in combating MDR periodontal pathogens: current research and future directions - Hashim, Nada Tawfig; Babiker, Rasha; Padmanabhan, Vivek; Islam, Md Sofiqul; Mohammed, Riham; Priya, Sivan Padma; Chaitanya, Nallan C. S. K.; Parveen Dasnadi, Shahistha; Ahmed, Ayman; Gobara Gismalla, Bakri; Rahman, Muhammed Mustahsen (Frontiers in Pharmacology, 2025)
Multidrug-resistant periodontal pathogens such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum present growing challenges to conventional antibiotic therapy, driving the search for alternative or adjunctive approaches. Polyphenolic compounds, derived from a wide range of plant sources, have emerged as promising candidates because of their antimicrobial, anti-inflammatory, and host-modulatory properties. A broad review of studies published between 2010 and 2025 highlights the multitargeted mechanisms of key polyphenols, including epigallocatechin-3-gallate, curcumin, resveratrol, and quercetin. These compounds disrupt bacterial membranes, inhibit efflux pumps, downregulate virulence genes, and interfere with quorum-sensing pathways and biofilm maturation, while also attenuating NF-κB signaling and pro-inflammatory cytokines. Several investigations demonstrate synergistic effects with antibiotics, enhancing membrane permeability, biofilm penetration, and dose-sparing efficacy. At the same time, advances in nanotechnology—such as nanoparticles, liposomes, mucoadhesive systems, and smart gels—have begun to overcome the inherent challenges of poor solubility, instability, and short oral residence that limit the therapeutic use of polyphenols. Despite these encouraging developments, variability in extraction methods, lack of standardization, and a scarcity of large, well-designed clinical trials remain significant obstacles to translation. Overall, the accumulating evidence suggests that polyphenols hold strong potential as sustainable adjuncts for managing resistant periodontal infections, offering dual benefits of antimicrobial activity and host modulation. Future progress will depend on harmonizing formulations, refining targeted delivery, and validating outcomes in robust clinical settings.